Exotic Devonian palynomorphs from the Sifa-1X well in the Western Desert, Egypt. (22nd April 2021) - Makled, Walid A.; Hints, Olle; Hosny, Atef M.; Shahat, Wafaa I.; Gentzis, Thomas
Abstract: The Devonian strata in the Western Desert of Egypt contain diverse plant and animal remains, in addition to the commonly reported miospores, acritarchs and chitinozoans. These remains are of significant paleoenvironmental and biostratigraphic value. This is the first study dedicated to recording these assemblages in the Devonian section in the Sifa-1X well. The zooclast assemblage described herein consists mainly of scolecodonts and remains of arthropods, notably eurypterids, arachnids and scorpions. The recovered scolecodonts belong to several species and likely three different families. The eurypterids are represented by several spines and exoskeleton cuticles. The shape and dimensions of the spines are analyzed and described. The spines vary in shape and size. A fragment of the arachnid Attercopus fimbriunguis was found in the Early Devonian. Additionally, fragments of scorpions were recovered, including pedipalp manus fragments of Compsoscorpius elegans and Corniops mapesii . The phytoclasts contain nematophytal cuticles and early plant tracheids. Some other fragments bear stomata and are attributed to the lycopsid Drepanophycus spinaeformis and the zosterophyllopsid Forania plegiospinosa . The nematophytes are represented by Nematothallus and Cosmochlaina cuticles and other tubular elements such as Porcatitubulus annulatus, Porcatitubulus spiralis, Constrictitubulus cristatus, Laevitubulus, Ornatifilum lornensis and Ornatifilum granulatum .